Comparison of Different Blood Transfusion Methods in Patients Undergoing Cesarean Section - Guo, Fei; Tang, Heshan; Wei, Xiaoqiang (Frontiers in Surgery, 2022)
Abstract Purpose: To compare the effect of allogeneic transfusion and acute normovolemic hemodilution (ANH) autologous transfusion in patients undergoing cesarean section. Methods: To observe patients who underwent cesarean section surgery and received blood transfusion in our hospital from February 2019 to July 2021, and were divided into allogeneic group and autologous group according to the blood transfusion method. Observe the vital signs, blood routine, T cell subsets, immunoglobulins, inflammatory factors and adverse reactions in the two groups. Results: There was no statistical significance in the intra-group and inter-group comparisons of HR, MAP, and SVV between the two groups before transfusion and transfusion for 10 min (P>0.05). 5d after operation, the RBC, PLT, HCT, and Hb of the allogeneic group were lower than those before operation, and the autologous group was higher than that of the allogeneic group (P<0.05). 5d after operation, the CRP, TNF-α, and IL-6 of the allogeneic group were higher than those before operation, and the autologous group was lower than that of the allogeneic group (P<0.05). 5d after operation, the CD4+, CD4+/CD8+ of the allogeneic group were lower than before operation, and the CD8+ was higher than before operation. The CD4+ and CD4+/CD8+ of the autologous group were higher than that of the allogeneic group, and CD8+ was lower than that of the allogeneic group (P<0.05). 5d after operation, the IgA, IgG, and IgM of the allogeneic group were lower than those before operation, and the autologous group was higher than that of the allogeneic group (P<0.05). During blood transfusion, there was no significant difference in the adverse reaction rate between the two groups (P>0.05). Conclusion: Both allogeneic transfusion and ANH autologous transfusion have little effect on the vital signs of patients undergoing cesarean section, but ANH autologous transfusion is more helpful to the stability of blood routine, T-cell subsets, immunoglobulin, and inflammation levels after surgery, which is a safe and effective way of blood transfusion.